PROSPECTS OF CREATION OF THE INDUSTRIAL PRODUCTION OF INSULATING INORGANIC MATERIAL "STTIZOL" - Pshinko, O. M.; Krasniuk, O. V.; Hrebennikov, V. M.; Palii, V. V.; Nakonechnyi, V. I.; Savytskyi, M. V. (Science and Transport Progress, 2007)
The article represents the analysis of use of thermal insulation materials inUkraineand shows advantages of newly developed inorganic thermal insulation material STTIZOL compared with conventional materials. Description of the main physical and mechanical properties of thermal insulation materials has been provided.